Investigating of the Psychological Health of Women Heads of Household - Mahshid Nouri; Mahmoud Minakari; Seyyed Jalal Sadrosadat; Shahriar Shahidi; Mahmoud Heidari (University of Social Welfare and Rehabilitation Sciences, 2003)
Objective: The present research investigates the state of psychological health in women who are heads of household and are under welfare protection by the Welfare Organization in Tehran province. The basic research question was whether or not the level of psychological health and its nine indicators according to SCL-90-R are different in women heads of house hold that are under welfare protection compared to women heads of house hold that are not under welfare protection. Materials & Methods: Subjects were over 180 women who were chosen randomly from four different areas in Greater Tehran. The instruments used in this study were SCL-90-R and a demographic questionnaire. A case-control cross sectional method was employed in the present study. Data were analyzed using single-case t-test, independent t-test, and multi-variant regression and Friedman test. Results: Results show that the mean score for psychological health and its nine indicators in the experimental group were significantly higher than the mean score for normal Iranian population (p=0.0009). This indicates that women who are heads of households in Iran are at a higher risk for psychological disorders. The strongest indicators of psychological disorder in these women were depression and psychosomatic complaints. Furthermore, women who are not under welfare protection are significantly more depressed than women who are under welfare protection (p=0.016). Conclusion: Factors which reliably predict women's psychological health are women's income, the income of family members and their own physical health. These results support previous in the field reiterating the fact special attention should be paid to the economical welfare and standards of living in these women.